The Genealogy of Political Currents and Its Relationship with Various Religious Readings after the Islamic Revolution - lafteh mansoori; Ahmad Ali Hesabi; Nabi’ollah Ider (توسعه اجتماعی, 2021)
The main purpose of this thesis is the genealogy of political currents and its relations to religious readings after the Islamic Revolution. To achieve this aim, the constitutional period untill now has been investigated, but with more emphasizing on political currents and their relation with religious readings. This research is based on Fairclough theory and its method including describing, interpreting and explaining the text along with Laclau and Mouffe theory and its method which includes identifying the meaning and text, time and place, semantic conflicts, and socio-political practices of political discourse. In this research three religious readings were examined from the constitutional period untill now. In each period these readings show themselves in different form and have selected a suitable describtion with the discourse but in spite of historical gap, these readings’ nodal points show no changes. In general, the purpose of this study is not to find solutions, but in the first place it tries to find clear describtion of the subject and at higher levels, to achive theoretical analysis, the relation between the social political currents and the basis of religious reading determined and finally genealogy of political currents were done. It became clear in this study that religious discourse is not an intrinsic task of pre - built, but it is made as a social reality by "language". The characteristic of this semantics is that it has nothing permanent. No religious discourse has been fully established in this study and has always been floating in range of complete fixation to instability & complete dislocation & this is the characteristic exclusivity & significance of ontology of discourse analysis theory that is based on this study.